SELF EFFICACY AND WORK STRESS IN SPECIAL EDUCATION TEACHER - Ayudia Popy Sesilia; Adelin Australiati Saragih (Jurnal Scientia, 2023)
Special teachers face various kinds of children with special needs, such as down syndrome, autism, and other emotional disabilities, causing teachers to experience chronic fatigue and stress. Teachers who teaching students with emotional disorders showed higher fatigue than those teaching students with intellectual disorders. The causes of educator stress in general are problems related to personal and classroom environment such as high workload and poor teaching conditions which trigger to low self-efficacy. Teachers with low self-efficacy show a greater tendency to leave work than teachers with higher self-efficacy. Educators with low self-efficacy influence enhance work stress level. This research aims ti study the effect of self efficacy on work stres in special education teacher. This research used quantitative approach with survey collecting data. The participants in this study were 84 special teachers from three special need schools. 87% female and 13% male teachers. The average age of teachers is 31 years old. Range of the tenure from 1- 27 years with an average of 21 years. The researcher collected data twice, work stress and self-efficacy scale in different time. Data analysis used regression analysis. The results showed a negative and significant effect of self-efficacy on job stress (b = -.39; p <.01) thus research hypotheses is accepted. Self-efficacy is important because it plays a role in how individuals understand themselves and believe in something that may and may not be achieved in their life.